Psychological resilience and its relationship to communication skills: A field study on a sample of students of the Faculty of Education at Damascus University - Aldroube, Reham Imad (Journal of Educational and Psychological Sciences, 2022)
The current study aims to know the relationship between psychological resilience and communication skills among a sample of students of the Faculty of Education at the University of Damascus, and whether there are statistically significant differences between the average degrees of psychological resilience and communication skills for males and females, as well as between the average scores of the sample members according to academic specialization and academic year. The study sample consisted of (140) male and female students, including (84) students from the Department of Psychology, and (56) students from the Department of Psychological Counseling. By Samer Radwan (Rudwan, 2018) The Communication Skills Scale was built based on previous studies. He also extracted for the two scales the necessary validity and reliability coefficients, and the results that resulted from the study, the existence of a statistically significant correlation between psychological resilience and communication skills. A high percentage, and this indicates a high degree of psychological flexibility among the students of the Faculty of Education at the University of Damascus, the members of the research sample. Medium percentage, and this indicates the presence of a medium degree of communication skills among students of the Faculty of Education at the University of Damascus, members of the research sample. In addition to the absence of statistically significant differences between the average scores of the sample members on the scale of psychological resilience and the scale of communication skills according to the gender variable, while there were statistically significant differences between the mean scores of the research sample according to the variable of the school year in favor of the fifth year on the scale of psychological resilience. There are no statistically significant differences between the average scores of the sample members according to the academic specialization, and the scale of communication skills, and the researcher interpreted these results in the light of the research data based on the theoretical framework and previous studies.